Dietary acrylamide and the risk of pancreatic cancer in the International Pancreatic Cancer Case–Control Consortium (PanC4). (11th November 2016) - Pelucchi, C.; Rosato, V.; Bracci, P. M.; Li, D.; Neale, R. E.; Lucenteforte, E.; Serraino, D.; Anderson, K. E.; Fontham, E.; Holly, E. A.; Hassan, M. M.; Polesel, J.; et al.
Abstract : Background: Occupational exposure to acrylamide was associated with excess mortality from pancreatic cancer, though in the absence of dose-risk relationship. Few epidemiological studies have examined the association between acrylamide from diet and pancreatic cancer risk. Patients and methods: We considered this issue in a combined set of 1975 cases of pancreatic cancer and 4239 controls enrolled in six studies of the Pancreatic Cancer Case–Control Consortium (PanC4). We calculated pooled odds ratios (ORs) and their 95% confidence intervals (CI) by estimating study-specific ORs through multivariate unconditional logistic regression models and pooling the obtained estimates using random-effects models. Results: Compared with the lowest level of estimated dietary acrylamide intake, the pooled ORs were 0.97 (95% CI, 0.79–1.19) for the second, 0.91 (95% CI, 0.71–1.16) for the third, and 0.92 (95% CI, 0.66–1.28) for the fourth (highest) quartile of intake. For an increase of 10 µg/day of acrylamide intake, the pooled OR was 0.96 (95% CI, 0.87–1.06), with heterogeneity between estimates ( I 2  =   67%). Results were similar across various subgroups, and were confirmed when using a one-stage modelling approach. Conclusions: This PanC4 pooled-analysis found no association between dietary acrylamide and pancreatic cancer.